Motivasi Petani dalam Pengelolaan Usaha Hutan Rakyat Desa Cingambul, Kecamatan Cingambul, Majalengka - Suherdi Suherdi; Siti Amanah; Pudji Muljono (Department of Communication and Community Development Sciences and PAPPI (Perhimpunan Ahli Penyuluhan Pembangunan Indonesia), 2014)
Private forests have economical, social and environmental benefits. Through the private forests, farmers can support the fulfillment of the household needs, included basic and social needs, as well as appreciation for their initiatives and actions in land rehabilitation. Without strong motivation from farmers, the private forests would be rarely found. Thus, the research objective is to analyze factors motivate farmers do the business and therole of the forests extension workers in the development of private forests. Primary data was collected in CingambulVillage, Sub-District Cingambul, Majalengka from July to August 2013. A number of 81 farmers out of 101 private forest farmers were selected as respondents. A Rank Spearman Correlation was used to analyse factors correlate to motivation of the farmers in running private forests. The research results show that: (1) farmers’ motivation has a positive correlation with the farmer’s perception to the benefits of private forests, attitudes of forest people toward their private forest business, availability of plant species, ease of marketing, frequency of forest extension workers visit, suitability of the material, equipment availability, and accuracy methods applied in the extension activity, and (2) the farmers perceived that the dominant roles of forestry extension are as a advisors, facilitators and as a educators. There is a need to improve the role of extension workers as a motivator for farmers in managing the private forests.Keywords: motivation, private forests, the role of forestry extension workers.